A comparative study on the maternal and foetal outcome between normal and high risk pregnancy patient - Sultana, Afroza; Roy, Beauty Rani; Mondal, Montosh Kumar; Yeasmeen, Sabina; Chowdhury, Saleha Begum (Journal of the Bangladesh Society of Anaesthesiologists, 2022)
Background Pregnancies and deliveries are potentially at risk. Well supervised antenatal, intranatal and postnatal care can reduce this risk to a minimal acceptable level. Objective To find out perinatal outcome of high-risk pregnant patients in comparison with the normal pregnant women and to evaluate the utility of numerical scoring system in identifying high-risk pregnancy. Methods 200 patients were selected from the admitted patients in the obstetric ward of Bangabandhu Sheikh Mujib Medical University, Dhaka. Study patients were divided into three groups: 100 patients (control group) were normal pregnancy (score 0-2), 85 patients were high-risk ( score 3 – 6), and 15 patients were severe-risk (score 7 or more). Both case and control subjects were followed intranatally and postnatally up to the discharge from the above institutions. All types of abnormalities or complications like prolonged ist stage, 2nd stage, APH, PPH and all types of operative and non operative interventions were recorded in order to correlate with perinatal mortality, morbidity and maternal morbidity. Each patient was followed up to discharge from the hospital and abnormalities important for the study were recorded. Neonatal morbidity was defined for surviving newborn by Apgar score <7 at 5 minutes or birth weight < 2.5 kg. Results In normal pregnancy group, 43% needed to be delivered by caesarean section in comparison to 63 (74.1%) and 14 (93.33%) patients respectively in high-risk and severe-risk group (P <0.001). Maternal complication following normal vaginal delivery was highest (100%) in severe-risk group, followed by highrisk group (36.36%) and normal pregnancy (19.30%). Complications following caesarean section were also highest in severe-risk group (28.47%), followed by normal pregnancy (25.59%) and high-risk pregnancy (20.63%). Neonatal complications in normal pregnancy group was 30.23% in comparison 38.46% in high risk group. 6 (6%) of neonates in the normal pregnancy group had Apgar score < 7 at 5 minutes and in high risk and severe-risk groups, 10 (11.76%) and 7 (43.75%) of the neonates respectively had Apgar score <7 at 5 minutes (P < 0.001). In the severe-risk group, 8 (50%) of the babies had birth weight <2.5kg, which is higher than high and normal pregnancy group, i.e. 25 (28.41%) and 3 (3%), respectively(P<0.001). Higher perinatal deaths also occurred in high-risk and severe risk groups. Conclusion It can be concluded that the perinatal morbidity, mortality and maternal morbidity are significantly higher in high-risk pregnancies. This group, though represent only 20-30 percent of all pregnant patients, is responsible for 70-80 percent of the perinatal morbidity and mortality. JBSA 2012; 25(2): 59-65